D8.10 Report on the ECoE Living Labs Program and analysis of effectiveness - Papoutsa, Christiana; Nisantzi, Argyro; Polydorou, Thomaida; Mamouri, Rodanthi-Elisavet; Varvaris, Ioannis; Neophytides, Stelios; Loulli, Eleni; Prodromou, Maria (My University, 2022)
This document, entitled “D8.10 Report on the ECoE Living Labs Program and analysis of effectiveness” provides a detailed description of currently ongoing developments pertaining to the Living Labs Program of the ERATOSTHENES Centre of Excellence (ECoE). In specific, Living Labs in two of the scientific thematic areas of the centre are currently under development, namely in the thematic areas of “Agriculture” and “Atmosphere”, both of which are presented in detail in this report. The role of each Living Lab and main End-user categories are discussed, along with infrastructure devoted to each Living Lab and the relative procedures that will enable access to interested parties.
Keywords: Remote Sensing; EXCELSIOR; ERATOSTHENES Centre of Excellence; Earth Observation; Digital Innovation Hub; EMMENA